Plan exportador de miel de la empresa Beela apicultura hacia los Estados Unidos (2021)
This research focuses on the search for a target market for the international commercialization of honey produced by the company Beela Apicultura, a company from Boyacá dedicated to the sale of products derived from beekeeping. Thus, from this, an export plan is developed in which a market analysis can be evidenced, as well as the main consumers and producers of honey worldwide, in such a way that the company can have a clear vision of who are your main competitors, the behavior of the market and potential buyers for your product.